Enhancing the user experience for an energy metering platform - The full process from problem identification to concept development - Bjöörn, Linnea (My University, 2025)
As energy consumption continues to rise, the need for effective tools that promote energy awareness and encourage sustainable behaviour has become increasingly important. This study explores how the user experience (UX) of energy metering data presentation in a digital platform can be enhanced and thereby support behavioural change toward energy efficiency. The project was conducted in collaboration with Elvaco, a company specializing in smart energy metering solutions, and focused on improving the user experience of their new digital platform, Play. The initial phase of this study involved problem identification through user research, market analysis and literature review to understand the key challenges of Elvaco’s digitalization. One aspect of the findings indicated that end users often are unexperienced regarding energy systems and lack knowledge of supporting insights and actionable recommendations, leading to limited behavioural change. By applying user-centred design principles, the study examined how end users interact with energy data and what design elements facilitate better understanding and decision-making. A combination of usability testing, interviews and prototyping in Figma was used to develop and evaluate approaches in presenting energy data in a clear and actionable way. Particular attention was given to behaviour-oriented design, including knowledge enhancement and decision-support tools, to motivate users toward more sustainable energy consumption. The results indicate that a well-structured, intuitive data presentation, combined with additional support and recommendations, significantly improves user engagement and the ability to take informed actions. This study contributes to the field of sustainable UX design by demonstrating how digital solutions can bridge the gap between energy awareness and behavioural change.
Keywords: Energy metering; Digitalisation; Sustainable behaviour; User experience; Energy awareness; User study; Concept development